Characterization of the complete chloroplast genome of Melaleuca cajuputi subsp. cumingiana (Myrtaceae). Issue 2 (1st February 2021) - Liang, Danhui; Zhu, Liming; He, Yuyu; Xiong, Xin
Abstract: Plants in the genus Melaleuca have been widely used as traditional medicine mainly because of their broad spectrum antimicrobial activity. In this study, we reported the complete chloroplast genome of Melaleuca cajuputi subsp. cumingiana . The chloroplast genome of this species is 158, 855 bp in length, including a pair of inverted repeat regions (IRs) (26, 727 bp) that is divided by a large single-copy (LSC) area (87, 338 bp) and a small single-copy (SSC) area (18, 063 bp). The circular chloroplast genome of M. cajuputi subsp. cumingiana contains 135 unique genes, composing of 87 protein-coding genes, 40 tRNA genes, and eight rRNA genes. Phylogenetic analysis indicates that M. cajuputi subsp. cumingiana was clustered with species in the tribe Melaleuceae. This complete chloroplast genome of M. cajuputi subsp. cumingiana will provide a powerful tool to accelerate breeding, biotechnological and phylogenetic study.